Preconception counseling for thyroid disorders - Aghajanian, Paola (Annals of Thyroid, 2018)
Thyroid disease is the most common endocrine disorder affecting women of reproductive age. Accordingly, women with thyroid dysfunction who are considering pregnancy should have preconception counseling to review the status of their thyroid health with a focus on improving future pregnancy outcomes. Goals of the preconception counseling visit include optimizing control of thyroid function prior to conception with an emphasis on the use of effective interval contraception. Discussion of the effects of thyroid disease on pregnancy and the influence of pregnancy on thyroid disease are helpful in setting accurate expectations for the antepartum period. A review of the safety profile of all available treatment options including any potential maternal and fetal side effects should be undertaken. Targeted TSH screening, treatment of those with serum TSH >4.0 mU/L, adjustment of levothyroxine dosage to achieve TSH